OPTICAL AND ELECTRICAL PROPERTIES OF GRAPHITE THIN FILMS PREPARED BY DIFFERENT METHODS - Solovan, Mykhailo M.; Yamrozyk, H. M.; Brus, Viktor V.; Maryanchuk, Pavlo D. (East European Journal of Physics, 2020)
The paper reports on the structural, optical and electrical properties of graphite thin films prepared by two methods: the vacuum-free method "Pencil-on-semiconductor" and via the electron beam evaporation. Graphite thin films prepared by the non-vacuum method has annealed at a temperature of 920K.The transmission spectra of the investigated graphite films and the electrical properties of these thin films were measured at T = 300 K. The value of the height of barriers Eb at the grain boundaries and the temperature dependence of the electrical conductivity in the range ln(σ·T1/2) = f(103/T) were determined, It is established that the height of the barrier at the grain boundaries for the drawn graphite films is Eb = 0.03 eV, for annealed Eb = 0.01 eV and for the graphite films deposited by the electron beam evaporation Eb = 0.04 eV, ie for annealed film the barrier height is the smallest. It is shown that graphite films deposited by the electron beam evaporation reveals the highest transmittance (T550 ≈ 60%), and the transmission of drawn films is the lowest, annealing leads to its increase. The minimum values ​​of transmission at a wavelength λ = 250nm are due to the scattering of light at the defects that are formed at the grain boundaries. Annealed graphite films have been found to possess the best structural perfection because they have the lowest resistivity compared to non-annealed films and electron-beam films and have the lowest barrier height. Simultaneous increase of transmission in the whole spectral range, increase of specific electrical conductivity and decrease of potential barrier at grain boundaries of the annealed drawn graphite film clearly indicate ordering of drawn graphite flakes transferred onto anew substrate, which led to the reduction of light scattering and the improvement of charge transport due to the larger area of ​​overlap between graphite flakes
Keywords: Type of access: Open Access; pencil-on-semiconductor; annealing; thin films; graphite; grain boundaries